2020
DOI: 10.2139/ssrn.3604094
|View full text |Cite
|
Sign up to set email alerts
|

Prosociality Predicts Health Behaviors during the COVID-19 Pandemic

Abstract: Socially responsible behavior is crucial for slowing the spread of infectious diseases.However, economic and epidemiological models of disease transmission abstract from prosocial motivations as a driver of behaviors that impact the health of others. In an incentivized study, we show that a large majority of people are very reluctant to put others at risk for their personal benefit. Moreover, this experimental measure of prosociality predicts health behaviors during the COVID-19 pandemic, measured in a separat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 82 publications
1
24
0
Order By: Relevance
“…Another interesting direction for future research is to link these types of giving with COVID-19 related health behaviors and engagement with government regulations. Recent studies in adults have namely demonstrated links between pandemic health behaviors and various forms of prosociality [39][40][41][42]. Finally, the novel Dictator Games provided a reliable measure of giving as was shown by significant correlations across time (i.e., r's .19-.57), although these correlations were lower than those of studies where Dictator Games to anonymous others were repeatedly administered in the same sitting (i.e., r's .70-.91).…”
Section: Peri-pandemic Giving To Othersmentioning
confidence: 99%
“…Another interesting direction for future research is to link these types of giving with COVID-19 related health behaviors and engagement with government regulations. Recent studies in adults have namely demonstrated links between pandemic health behaviors and various forms of prosociality [39][40][41][42]. Finally, the novel Dictator Games provided a reliable measure of giving as was shown by significant correlations across time (i.e., r's .19-.57), although these correlations were lower than those of studies where Dictator Games to anonymous others were repeatedly administered in the same sitting (i.e., r's .70-.91).…”
Section: Peri-pandemic Giving To Othersmentioning
confidence: 99%
“…Consequently, in recent years behavioral scientists have started using norm-based interventions to promote desirable behavior in economic experiments (D'Adda et al, 2017;Bicchieri & Xiao, 2009;Bilancini et al, 2020;Capraro & Rand, 2018;Capraro & Vanzo, 2019;Eriksson et al, 2017;Krupka & Weber, 2009;Krupka & Weber, 2013;Kimbrough & Vostroknutov, 2016) as well as in the field (Agerström et al, 2016;Croson et al, 2010;Ferraro & Price, 2013;Frey & Meier, 2004;Goldstein et al, 2008;Allcott, 2011;Hallsworth et al, 2017;Allcott & Kessler, 2019). Moreover, several recent works have highlighted the social motives behind COVID-19 prevention behavior (Campos-Mercade et al, 2020;Lees et al, 2020;Raihani & de-Wit, 2020). This suggests that norm-based interventions may be useful in promoting pandemic responses (Van Bavel et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…We believe such spillovers to be less relevant for the socioeconomic variables, which we asked about after the choice experiment.7 We also asked a set of questions measuring their risk, time, and social preferences using the well-established questions fromFalk et al (2018). These questions are used in another research project unrelated to the choice experiment(Campos-Mercade et al, 2020).…”
mentioning
confidence: 99%